Consumption Behavior of Fisherman Family in Tiku Selatan Village, Tanjung Mutiara District, Agam Regency, West Sumatera Province - Rizki Saidinia Ali; Firman Nugroho; Lamun Bathara (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
The purpose of this study was to determine the characteristics of the fishermen's families in South Tiku Village, to determine the consumptive behavior of the fishermen's families in South Tiku Village. The research method used in this study is a descriptive quantitative research method, namely by seeking information about the symptoms of consumptive behavior of fishermen's families in Tiku Selatan Village or with this method clearly supporting the goals to be achieved, planning the approach, collecting data as material for making reports. The results showed that the level of consumptive behavior of fishermen's families was grouped with consumptive (32-48) and non-consumptive (16-31) scores.Determination of variable categories based on the number of indicator items each with a total of 16 indicators, 47 respondents, 3 categories with a maximum score of 2256 and a minimum score of 752. The results show that from 47 fishing families in Tiku Selatan village 96% behave consumptively (45 people) and 4% are not consumptive (2 people).